2014
DOI: 10.1007/s12010-014-1161-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrate Injection on Microbial Enhanced Oil Recovery and Oilfield Reservoir Souring

Abstract: Column experiments were utilized to investigate the effects of nitrate injection on sulfate-reducing bacteria (SRB) inhibition and microbial enhanced oil recovery (MEOR). An indigenous microbial consortium collected from the produced water of a Brazilian offshore field was used as inoculum. The presence of 150 mg/L volatile fatty acids (VFA´s) in the injection water contributed to a high biological electron acceptors demand and the establishment of anaerobic sulfate-reducing conditions. Continuous injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Using a packed-bed bioreactor, the same study found that souring control in a reactor that received 12.5 mM lactate required the addition of 10 mM nitrate, irrespective of the sulfate concentration. Thus, if the (usable) oxidative capacity of organics, such as lactate or VFAs, is larger than the reductive capacity of nitrate added to the injection water ( da Silva et al, 2014 ), most of the organics will remain in the water phase by the time the denitrification process is completed, creating ideal conditions for sulfate reduction. This is not inconsistent with observations from the LC and HC systems.…”
Section: Discussionmentioning
confidence: 99%
“…Using a packed-bed bioreactor, the same study found that souring control in a reactor that received 12.5 mM lactate required the addition of 10 mM nitrate, irrespective of the sulfate concentration. Thus, if the (usable) oxidative capacity of organics, such as lactate or VFAs, is larger than the reductive capacity of nitrate added to the injection water ( da Silva et al, 2014 ), most of the organics will remain in the water phase by the time the denitrification process is completed, creating ideal conditions for sulfate reduction. This is not inconsistent with observations from the LC and HC systems.…”
Section: Discussionmentioning
confidence: 99%
“…A biocide, acrolein, was also applied in weekly batches to treat the injection lines and prevent nitrate-fed biofilm After one month of treatment, H2S in the produced gas from one gathering system decreased from an average of 170 ppmv to 110 ppmv. A corresponding decrease in H2S in the produced water was observed [14] Column experiments to investigate the effects of nitrate injection on SRB inhibition and MEOR Resulted in significant sulfide control (40-100% reduction) within few days [84] Nitrite Using up-flow packed bioreactors both nitrate and nitrite are effective sulfide removers Nitrite is a stronger SRB inhibitor. Nitrate gives less SRB inhibition, because it is only partially converted to nitrite [82] Testing various inhibitors among them nitrite in full field numerical simulations 1 mM of nitrite can reduce souring by 92%, while perchlorate (1 mM) or nitrate (1 mM) reduce sulfide accumulation by 57% and 80% respectively [97] Molybdate Batch/dynamic experiments and field test as a part of a MEOR project; a Na2MoO4 concentration of 0.5 mM was found as optimum Molybdate inhibited the activity of SRB efficiently, while still enabling MEOR due to its specific inhibition mechanism.…”
Section: Chemical/application Mode Conclusion Ref Nitratementioning
confidence: 99%
“…Nitrate-enhanced MIEOR has shown promising outcomes in stimulating the growth of biosurfactant-producing bacteria in reservoir conditions (Da Silva et al, 2014;Gassara et al, 2017). The microbial communities generated in the reservoir tend to vary through the various MIEOR stages.…”
Section: Microbe Classificationsmentioning
confidence: 99%